An Adverse Reaction in the Pediatric Sleep Laboratory - Diana Reppucci; Debra Medin; Suhail Al-Saleh; Mary Jane Smith; Jill Barter; Reshma Amin (Canadian Respiratory Journal)
We present a case of a 15-month-old boy with Cornelia de Lange Syndrome (NIPBL gene mutation). On a PSG, central sleep apnea (central apnea-hypopnea index of 19/hour) and nocturnal hypoventilation (transcutaneous CO2 > 50 mmHg for 53% of the night) were found. A positive pressure initiation study was aborted because the patient developed a serious adverse reaction. The differential diagnosis included a skin fragility condition versus an allergic contact dermatitis to the interface; this could be from the povidone-iodine solution used to clean the NiPPV interface or from the plastic of the interface itself. A skin biopsy was performed which was normal. The reaction was likely secondary to an allergic contact dermatitis from the povidone-iodine solution used to clean the NiPPV interface. The patient is currently tolerating NiPPV.